2006
DOI: 10.1590/s0100-83582006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant row spacing and herbicide use on weed aboveground biomass and corn grain yield

Abstract: -The use of narrow plant spacing in corn (Zea mays) has been suggested as a technological alternative to obtain grain yield increases, due to a better use of resources. The regular pattern could diminish intraspecific competition while favoring interspecific competition with weeds. The objective of this study was to analyze the effect of corn row spacing on weed aboveground biomass and corn grain yield. Field experiments were conducted during 2002/ 2003 and 2003/2004 growing seasons. Three corn hybrids with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
1
16
2
Order By: Relevance
“…Also, dense planting increased ears, stover and total yields by 25.07, 30.94 and 28.55 %, respectively. These results are in agreement with those reported by other investigators of them Porter et al (1997), Bavec & Bavec (2002), Widdicombe &Thelen (2002, Acciares & Zuluaga (2006), Maddonni et al (2006), Singh & Singh (2006) and Williams et al (2014). But, Abouziena et al (2008) found that the highest 100-grain weight and grain weight/ ear were recorded when maize was planted with low plant population.…”
Section: Weed Control Effectsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, dense planting increased ears, stover and total yields by 25.07, 30.94 and 28.55 %, respectively. These results are in agreement with those reported by other investigators of them Porter et al (1997), Bavec & Bavec (2002), Widdicombe &Thelen (2002, Acciares & Zuluaga (2006), Maddonni et al (2006), Singh & Singh (2006) and Williams et al (2014). But, Abouziena et al (2008) found that the highest 100-grain weight and grain weight/ ear were recorded when maize was planted with low plant population.…”
Section: Weed Control Effectsupporting
confidence: 92%
“…On the other hand, Acciares & Zuluaga (2006) indicated that weeded treatments and higher planting density resulted the highest grain yield in comparison to un-weeded and lower planting density. Also, Widdicombe & Thelen (2002) stated that yield increased up to 10% by increasing planting density.…”
mentioning
confidence: 94%
“…This less competition led to more uniform root and leaf distribution that promoted more effective interception of PAR (IPAR) and moderate density favored better utilization of intercepted light. Acciaresi and Zuluaga (2006) reported that the grain yields were 30 and 33 per cent higher under 35 × 35 cm pattern over 70 × 17.5 cm, respectively. Fanadzo et al (2010) also reported that closer square planting of 45 × 38 cm recorded higher green cob yield and grain yield (33460 and 12547 kg ha -1 , respectively) than rectangular pattern of 90 × 19 cm at eastern Cape, South Africa.…”
Section: Maize Grain Yieldmentioning
confidence: 97%
“…Maddonni et al (2001a) have detected that maize leaf orientation could react to filling empty spaces (e.g., intra or inter-row) due to plant spatial arrangement. Acciaresi and Zuluaga (2006) reported that in clay loamy soils, the grain yield was 30 and 33 per cent higher under 35 × 35 cm pattern over 70 × 17.5 cm, respectively. Fanadzo et al (2010) indicated that closer square planting of 45 × 38 cm recorded higher green cob yield and grain yield than rectangular pattern of 90 × 19 cm at Eastern Cape, South Africa.…”
Section: Introductionmentioning
confidence: 96%
“…When irrigation water is used to supplement rainwater the overall water productivity is improved (Oweis and Hachum, 2012). Several studies has linked row spacing to plant growth and soil water storage (Eberbach and Pala, 2005;Acciaresi and Zuluaga, 2006;Onyango, 2009;Pandey et al, 2013). Rainwater harvesting applied to dry areas is usually implemented with wider catchments hence the traditional IRWH was initially tested on 2 m to 20 m row spacing.…”
mentioning
confidence: 99%